New Report on Hydra viridissima Pallas, 1766 (Cnidaria, Hydrozoa, Hydridae) from Chingleput Lake, Tamil Nadu- India - Ramanibai R (Journal of Research in Biology, 2011)
Hydra viridissima Pallas, 1766, a green colour fresh water polyp is well known for over 200 years for its remarkable regenerative capacity. New informations on the genus Hydra collected from Kolavoi Lake, Chingleput is reported here with its morphometric features.This is the first report on the occurrence of Hydra viridissima (Pallas, 1766) from the Kolavoi Lake, Chingleput.Tamil Nadu - India